ANALISIS PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL, STRUKTUR KEPEMILIKAN INSTITUSIONAL DAN PROFITABILITAS TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2017-20 - Yamin, Mohammad; Indah Pertiwi, Novia (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2023)
ABSTRACT This study aims to determine the effect of Managerial Ownership Structure, Institutional Ownership Structure, and Profitability on Accounting Conservatism in Manufacturing Companies in the Basic Industry and Chemical Sector listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The data used using purposive sampling. Where 14 companies were obtained as a sample from a population of 75 manufacturing companies in the basic and chemical industry sectors. The research method used in this study is multiple linear regression with the classical assumption test requirements, followed by partial significance by using the hypothesis test, namely the T test while to find out simultaneously using the F test with a significance level of 5%. This study shows partial results (T test), managerial ownership structure variable has no significant effect on accounting conservatism, institutional ownership structure has a positive and significant effect on accounting conservatism, and profitability has a negative and significant effect on accounting conservatism. And for the simultaneous research results (F test) show the results of managerial ownership structure, institutional ownership structure and profitability simultaneously influence accounting conservatism. In addition, the predictive ability of the three independent variables on accounting conservatism can be seen from the coefficient of determination of 16%, while the remaining 84% is explained by other variables that were not examined outside the research model.